PENGARUH KALIUM NITRAT TERHADAP PERTUMBUHAN DAN HASIL BERBAGAI VARIETAS SELADA SISTEM HIDROPONIK NUTRIENT FILM TECNIQUE (NFT): AB Mix, Hidroponik, Kalium Nitrat, Selada - Septino, Indrat; Ratna Nurhayati, Dewi; Sigit Saputro, Avisema (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2025)
Lettuce has a very large market opportunity, the high demand in the market makes lettuce plants have a high economic value. The objectives of this study include, to obtain the appropriate concentration of KNO3 fertilizer for several varieties of lettuce using the Nutrient Film Technique NFT hydroponic system, to obtain suitable varieties for the application of KNO3 fertilizer using the NFT system, to obtain the interaction between varieties and KNO3 fertilizer with the NFT system. This study was conducted from June to August 2024 at the ARD Farm Nogosari garden, Boyolali with an altitude of ± 152 meters above sea level. The tools and materials used, NFT hydroponic installation, seedling trays, rockwool, AB Mix nutrients, stationery. The research design used in the study was a Split Plot design consisting of 2 treatment factors, the main plot of concentration and the seedling plot is a variety. The first factor is the concentration of KNO3, 1 gr/L (AB Mix 800 ppm + 1 gr/L KNO3), KNO3 2 gr/L (AB Mix 800 ppm + 2 gr/L KNO3), KNO3 3 gr/L (AB Mix 800 ppm + 3 gr/L KNO3). The second factor is the type of lettuce variety, Matt green, Romaine, Grand rapids. The combination of treatments consisted of 9 combinations and was repeated 3 times. The results and observation data were analyzed using Analysis Of Variance, if significantly different, continued with the BNJ test at a level of 5%. Potassium nitrate fertilizer did not affect all observation parameters, the appropriate variety for potassium nitrate fertilizer was the matt green variety on leaf width, there was no interaction between potassium nitrate fertilizer and variety.